Implementasi Penggunaan Aplikasi Sisekuedes dalam Pengelolaan Keuangan Desa didesa Pijot Utara Kecamatan Keruak Kabupaten Lombok Timur Tahun 2024 - Yuniar Affandy; Salmi Yuniar Bahri; Rabiatul Adawiyah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2023)
This study explores the implementation of the SiskeuDes application in financial management in Pijot Utara Village. SiskeuDes, as a village financial information system, aims to improve the efficiency, transparency, and accountability of village financial management. This study identifies and analyzes the stages of SiskeuDes use, namely planning, implementation, administration, and reporting, and evaluates the advantages and disadvantages of the system in the village context. At the planning stage, SiskeuDes assists in the preparation of planning documents such as RKPDes and APBDes through village deliberations involving village officials and the community. This system supports the accuracy and efficiency of budget planning despite challenges such as network disruptions and HR skills. At the implementation stage, SiskeuDes facilitates verification and budget preparation and reporting, with the active role of the Village Secretary and the Village Financial Management Unit (UPKD). Financial administration has also progressed thanks to this system, which reduces the risk of manipulation and increases transparency. The reporting and accountability process is carried out in a structured and integrated manner with SiskeuDes, although there are obstacles in conveying information to the community. The advantages of using SiskeuDes include increased efficiency of financial recording and reporting, real-time transparency, and support for community participation. However, disadvantages include limited infrastructure, suboptimal HR skills, and challenges in delivering information to the community. Improvement efforts such as increasing training and improving infrastructure are being made to address these shortcomings. Overall, SiskeuDes has made a positive contribution to village financial management, but still requires adjustments to address the various challenges that exist.